Investigation of the dependence of multiple recollision on laser wavelength in the nonsequential double ionization process. Issue 1 (May 2021) - Truong, Thu D H; Quach, Mi A; Nguyen, Hanh H; Nguyen, Uyen T; Dung, Do Hung; Pham, Vinh N T
Abstract: This paper investigates the recollision dynamics of the nonsequential double ionization process induced by linearly polarized laser pulses with the three-dimensional classical ensemble model. The results show that the correlated two-electron momentum distribution is contaminated by the double recollision events for sufficiently short laser wavelength. When the laser wavelength increases from near-infrared to mid-infrared, the single-recollision events are more prominent than the double-recollision one. Moreover, the mechanisms governing the nonsequential double ionization process are also thoroughly studied in the case of double-recollision.